Changing the Stigma of Women's Beauty Through an International Contest for People with Disabilities - Priyanka, Gita; Sagena, Uni W. (LifeSciFi, 2024)
Miss Wheelchair World is a very different international competition and raises the theme of equality for people with physical disabilities, especially women. This pageant provides an opportunity for women with disabilities from various countries to participate and inspire the world. This research method uses descriptive research methods, namely explaining how people with disabilities struggle to change the stigma of beauty through the Miss Wheelchair World international beauty contest, using secondary data in the form of books, journals, theses, research results and articles published via the internet. The Miss Wheelchair World pageant has a theme of equality for people with physical disabilities and aims to change the stigma of beauty in the world. This contest is an effort for people with disabilities to fight the problems they often face, such as discrimination, lack of accessibility, and stigma created by media and technology. With the aim of reducing common problems, the pageant has made various efforts to change the stigma associated with disabilities, such as empowerment and representation, sharing experiences, concrete actions, and connecting communities.